A Reforma da Educação na Ditadura Militar (1964-1971): a influência ideológica do regime como violação de direitos fundamentais e humanos - Leal Junior, Antonyo (2020)
The dissertation “Education reform in the military dictatorship (1964- 1971): The influence of the regime as a violation of fundamental and human rights”, developed at the State University of Western Paraná - UNIOESTE, campus of Cascavel / PR, on the line “Education, Social Policies and State”, aims to analyze how the ideological influence of the regime, especially that of national security, influenced the normative reformulation of the educational system that caused the violation of fundamental and human rights. To develop it, it relied on documentary research, with an emphasis on documents: Institutional Acts, 1967 Constitution, 1969 Constitution, Laws, Decree-laws and Decrees. The theoretical support for analyzing them takes into account the theory of Pierre Bourdieu, based on structuralist constructivism, which takes into account in the analysis of social relations the field, habitus and symbolic violence as a way of demonstrating how dominant groups overlap with groups dominated. It was found that reforms in the educational system were carried out, due to national security, to stem the communist threat in the country, as well as to structure national economic development through school education aimed at training manpower to satisfy the need of the capitalist system. Such movements, as they are not accepted by society, resulted in the practice of illegal conduct, as is the case with torture and illegal prisons, resulting in the violation of fundamental and human rights, such as life, freedom and education.